German Memory Discourse in a European Context: An Impressive Collection of Current Literary Research Before and After the Wende (KULT_online, 2009)
This anthology assembles a wide variety of essays on post-unification German literature and film pertaining to "the three areas of identity, memory, and Berlin literature" (p. 10). The volume is remarkable for its numerous and diverse topics coming from the perspectives of literary and cultural studies as well as from other social science disciplines. The appeal of this collection lies furthermore in its balanced inclusion of both established and new scholarly voices, including the youngest of university researchers. The anthology truly fulfills its ambitious goal of framing cultural memory and the search for identity in united Germany.